Characteristics of frequent users of the emergency department with chronic pain. Issue 3 (May 2020) - Shergill, Yaadwinder; Rice, Danielle; Smyth, Catherine; Tremblay, Steve; Nelli, Jennifer; Small, Rebecca; Hebert, Guy; Singer, Lesley; Rash, Joshua A.; Poulin, Patricia A.
ABSTRACT: Objectives: To identify the proportion of high-frequency users of the emergency department (ED) who have chronic pain. Methods: We reviewed medical records of adult patients with ≥ 12 visits to a tertiary-care, academic hospital ED in Canada in 2012-2013. We collected the following demographics: 1) patient age and sex; 2) visit details – number of ED visits, inpatient admissions, length of inpatient admissions, diagnosis, and primary location of pain; 3) current and past substance abuse, mental health and medical conditions. Charts were reviewed independently by two reviewers. ED visits were classified as either "chronic pain" or "not chronic pain" related. Results: We analyzed 4, 646 visits for 247 patients, mean age was 47.2 years (standard deviation = 17.8), and 50.2% were female. This chart review study found 38% of high-frequency users presented with chronic pain to the ED and that women were overrepresented in this group (64.5%). All high-frequency users presented with co-morbidities and/or mental health concerns. High-frequency users with chronic pain had more ED visits than those without and 52.7% were prescribed an opioid. Chronic abdominal pain was the primary concern for 54.8% of high-frequency users presenting with chronic pain. Conclusions: Chronic pain, specifically chronic abdominal pain, is a significant driver of ED visits among patients who frequently use the ED. Interventions to support high-frequency users with chronic pain that take into account the complexity of patient's physical and mental health needs will likely achieve better clinical outcomes and reduce ED utilization.